Deployment variables in the configurations structure third line (Journal of the College of Basic Education, 2022)
The current research dealt with (the cleavage variables in the structure of Thuluth calligraphy formations) in an attempt to study the cleavage property of (periods, withdrawals, and letters) of the Thuluth calligraphy letters that were inspired by Islamic art, with its constructive conceptual references and benefit from the variables of this property in Thuluth calligraphy formations, and the diversity of their employment in the constructivism of the work Calligraphy in the form of ideas and contents (the text), and referring it from its functional (notational) privacy to the aesthetic (decorative) privacy envisaged from the characteristics and rules of Arabic letters and their origins. As the Arabic calligraphy was associated with the Qur’anic texts and the honorable hadiths of the Prophet and the stages of their functional and aesthetic improvement, which led to the diversity of the structure of the Arabic calligraphy and the multiplicity of its forms.